Pregnancy e-health: a multicenter Italian cross-sectional study on internet use and decision-making among pregnant women. Issue 12 (26th September 2013) - Bert, Fabrizio; Gualano, Maria Rosaria; Brusaferro, Silvio; De Vito, Elisabetta; de Waure, Chiara; Torre, Giuseppe La; Manzoli, Lamberto; Messina, Gabriele; Todros, Tullia; Torregrossa, Maria Valeria; Siliquini, Roberta
Abstract : Background: Our study aimed to estimate the prevalence of pregnancy e-health seekers in a large Italian sample; to explore the factors influencing the choices of the childbearing women regarding their lifestyles after internet consultation; and finally to investigate potential differences between primiparous and multiparous women in internet use to find information about pregnancy. Methods: A multicentre survey was carried out in seven Italian cities. Data were collected through a validated questionnaire administered in waiting rooms of outpatient departments by medical doctors. Respondents were questioned about their sociodemographic status, their use of the internet to seek pregnancy information and their consequent choices to modify their lifestyles. Data were analysed using descriptive statistics and logistic regression. Results: Almost all women were pregnancy e-health seekers (95%), including those who also received information from healthcare professionals. Indeed, the main reason for searching the web was the need of further knowledge on pregnancy-related topic, over and beyond other key advantages of the net such as anonymity, simplicity and rapidity. A higher likelihood of changing lifestyle after pregnancy e-health was observed among the women who searched institutional websites; declared more confidence in the information retrieved; participated into pregnancy-centred forum online; and were residents in Italy. Conclusions: To reduce the likelihood for women of both finding erroneous information or misinterpreting correct ones, healthcare professionals should commit to fill the information gap and guide pregnant women in the online searches. Also, future studies are strongly needed to analyse the quality and accuracy of health information found on the web.